Cholesterol and alpha-tocopherol contents of fish and other seafood from the Straits of Malacca - Azlan, Azrina; Abd. Aziz@Mughni, Nurnadia; Khoo, Hock Eng; Ismail, Amin; Al-Sheraji, Sadeq Hassan; Razman, Muhammad Rizal (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
This study was conducted to determine the cholesterol and alpha-tocopherol contents of 20 marine fish and four other seafood from the Straits of Malacca. Cholesterol and alpha-tocopherol contents of the fish and other seafood were determined using high-performance liquid chromatography. The results showed that most of the fish contained low amounts of cholesterol, except sixbar grouper (Epinephelus fasciatus), long-tailed butterfly ray (Gymnura sp.), yellowstripe scad (Selaroides leptolepis), cuttlefish (Sepia officinalis), large-scale tongue sole (Cynoglossus arel), and longtail shad (Hilsa macrura) that contained high amounts of cholesterol (119.39-353.97 mg/100 g wet samples). Indian mackerel (Rastrelliger kanagurta), giant seaperch (Lates calcarifer), prawn (Metapenaeus affinis), and moonfish (Trachinotus blochii) had high alpha-tocopherol contents (462-989 μg/100 g wet sample). Regular consumption of fish and other seafood is highly recommended partly due to the high alpha-tocopherol content. Due to the high cholesterol in certain types of fish, consumption of the fish fillets of sixbar grouper, long-tailed butterfly ray, yellowstripe scad, cuttlefish, and large scale tongue sole should be <100 g per day and <50 g per day for longtail shad. Validation of the analytical method also showed a high accuracy and reproducibility of the HPLC method.